Breeding experience, but not mate retention, determines the breeding performance in a passerine bird. (31st March 2016) - Lv, Lei; Komdeur, Jan; Li, Jianqiang; Scheiber, Isabella B.R.; Zhang, Zhengwang
Lay Summary: Individuals that breed with the same mate often perform better than conspecifics that switch mates. This, however, may be due to the new mate having less breeding experience. We found that hair-crested drongos did not benefit from keeping former partners in terms of reproductive success, but breeding experience, particularly that of the male, was more important in determining breeding performance in this species. Abstract: Individuals that retain their former partners often perform better than conspecifics that switch partners. This may be due to high-quality individuals being more faithful to their partners and more productive. Investigations of the fitness benefits of mate retention that also control for potential confounding effects of individuals are scarce. We studied the influence of mate retention and breeding experience on breeding performance of the hair-crested drongo ( Dicrurus hottentottus ) by carrying out both cross-sectional and longitudinal analyses. Pairs with longer pair-bond duration did not fledge more young or fledglings of better body condition nor did they produce more or better fledglings than newly formed pairs consisting of at least 1 experienced breeder, that is, individuals that had bred before. Individuals produced fewer fledglings when they were paired with an inexperienced breeder, especially when females were paired with inexperienced males. Although clutch size was not affected by mate retention or breeding experience, pairs consisting of inexperienced breeder(s) had a relatively higher predation rate of eggs and/or nestlings because they may be less effective in nest defense. The onset of breeding was advanced in the year following mate retention, but not in the second year thereafter, when pairs still remained together. Furthermore, only the breeding experience of the male determined the onset of breeding: Pairs consisting of inexperienced males bred later in the season. Our results suggest that breeding experience, and particularly the breeding experience of the male, but not mate retention, is important in determining the breeding performance of hair-crested drongos.